Methods and TechniquesTransfemoral transcatheter aortic valve implantation in a patient with a severe aortic stenosis and cardiogenic shock requiring intra-aortic balloon pump support - Chodór, Piotr; Wilczek, Krzysztof; Przybylski, Roman; Świątkowski, Andrzej; Głowacki, Jan; Kalarus, Zbigniew; Zembala, Marian (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
The following paper presents a patient with severe aortic stenosis and severely reduced left ventricular ejection fraction with intra-aortic balloon pump counterpulsation support, who underwent transfemoral aortic valve implantation of a CoreValve prosthesis.